Skriften der forsvandt - Louise Karoline (Temp - tidsskrift for historie, 2024)
On May 10, 1875, the Danish Ministry for Education and Ecclesiastical Affairs decided to end the teaching of handwriting in Gothic script in Danish schools. From then on, pupils were to be taught to write only in Latin script. This article examines the circumstances surrounding the transition from Gothic to Latin handwriting in Denmark in the late 19th century. The motivation for the change was to improve student’s general writing skills by teaching a single alphabet rather than two. The initiative for the change, however, came from Denmark’s teachers who argued that the Latin script was easier and that teaching only one script would save precious time. Nonetheless, practical circumstances delayed the change. I discuss whether the discontinuation of Gothic writing can be linked to the prevailing national identity politics brought on by the Schleswig Wars. While the shift from Gothic writing could possibly be seen as an identity-political act to distance Danish culture from German influence after Denmark’s defeat in the Second Schleswig War, the transition to Latin was more likely an attempt to move culturally closer to the rest of Scandinavia.